Ecological Narratives in Dayak Tamambaloh Farming Mantras - Eligia Wijaya; Chairil Effendy; Martono; Sesilia Seli; Antonius Totok Priyadi; Ikhza Mahendra Putra (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2026)
The farming mantras of the Dayak Tamambaloh community embody ecological knowledge that reflects Indigenous relationships with nature and has been transmitted across generations through oral tradition. This study examines the ecological narratives embedded in these farming mantras and explores how they function as a medium of environmental communication. A descriptive-interpretive qualitative approach was employed using farming mantra texts and in-depth interviews with a purposively selected customary informant. Data were collected through observation, interviews, and documentation and analyzed using the Miles and Huberman interactive model, informed by Garrard’s ecocritical perspective and Cox’s environmental communication framework. The findings reveal three interconnected ecological narratives: respect for nature, human–nature harmony, and environmental sustainability. These narratives position farming mantras as a cultural medium for transmitting ecological knowledge, environmental ethics, and customary values across generations. This study contributes to Indigenous environmental communication scholarship by demonstrating how oral literature functions as a medium for conserving and transmitting local ecological knowledge, thereby extending ecocritical understandings of Indigenous environmental practices. Because the analysis focuses on one key informant within a single ritual system, the findings should be understood as context-specific rather than broadly representative of all Dayak communities.